The influence of MBE and device structure on the electrical properties of GaAs HEMT biosensors *Project supported by the National Key Research and Development Program of China (No. 2017YFB0405400), the Open Research Fund Program of the State Key Laboratory of Virology of China (No. 2017IOV002), the National Natural Science Foundation of China (Nos. 61274049, 61404130, 61574140), and the Shenzhen Science and Technology Innovation Commission (No. JSGG20160608100922614). (December 2018) - Luo, Jiaming; Guan, Min; Zhang, Yang; Chen, Liqiang; Zeng, Yiping
Abstract: High electron mobility transistors (HEMT) have the potential to be used as high-sensitivity and real-time biosensors. HEMT biosensors have great market prospects. For the application of HEMT biosensors, the electric properties consistency of the inter-chip performance have an important influence on the stability and repeatability of the detection. In this research, we fabricated GaAs/AlGaAs HEMT biosensors of different epitaxial structures and device structures to study the electric properties consistency. We study the relationship between channel size and consistency. We investigated the distribution of device current with location on 2 inch GaAs wafer. Based on the studies, the optimal device of a GaAs HEMT biosensor is an A-type epitaxial structure, and a U-type device structure, L = 40 μ m, W = 200 μ m.